Dissolved inorganic nitrogen and phosphorus dynamics in seawater following an artificial Saharan dust deposition event - Louis, Justine; Bressac, Matthieu; Pedrotti, Maria L.; Guieu, Cécile (Frontiers in Marine Science, 2015)
The dynamics of dissolved inorganic nitrogen and phosphorus in seawater after a dust event were followed to better understand the impact of dust deposition in low nutrient waters of the Mediterranean Sea. Three independent abiotic experiments were performed over three seasons (winter, spring, end of summer) characterized by contrasted biogeochemical conditions. Experiments consisted of seeding evapocondensed Saharan dust at the surface of a polyethylene tank filled with filtered surface seawater. Phosphate (PO3−4), nitrate (NO−3), size and number of particles and transparent exopolymeric particles production (TEP) were measured over the course of 1 week following seeding. Dust deposition was followed by a transient increase in [PO3−4] during the first 3 h with a maximum input of 33, 9, and 39 nM, respectively in May, October and February. The removal of almost all the PO3−4 initially released suggests a scavenging process of PO3−4 back onto ferric oxide-rich particles leading to concentrations at the end of the experiment close to the initial values (7 nM in May and October, and 6 nM in February). NO−3 released from dust was high especially in May and October (maximum input of 23 and 11 μM, respectively) and was attributed to nitrogen dissolution from the large amount of small particles (<1 μm) rich in nitrogen in the evapocondensed dust. [NO−3] remained high until the end of the experiment (16 μM in May and 11 μM in October), indicating that NO−3 from dust is likely to be bioavailable for a longer period compared to PO3−4 from dust. The release of PO3−4 and NO−3 was intrinsically linked to particle dynamics, governed by the quality/quantity of dissolved organic matter.